2012
DOI: 10.1002/ps.3409
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic larvicidal effect and morphological alterations induced by ethanolic extracts of Annona muricata and Piper nigrum against the dengue fever vector Aedes aegypti

Abstract: It is suggested that the different mechanisms of action of the larvicidal actives A. muricata acetogenins and P. nigrum piperamides explain the observed synergism. The combination of inexpensive botanicals and a low-cost organosolvent such as ethanol leads to a simple and efficient phytolarvicidal formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…In addition, the larvae of the Aedes aegypti mosquito, the transmitters of dengue fever, elicited high susceptibility to the ethanolic extract of the seeds with the LC 50 of 224.27 ppm [ 127 ]. A. muricata seeds showed more than five times synergistic larvicidal activity when combined with Piper nigrum fruit ethanolic extracts ( A. muricata 90:10 P. nigrum ) [ 128 ]. The fractionation analysis of the extract showed that n -hexane is the most active fraction with an LC 50 of 73.77 ppm.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…In addition, the larvae of the Aedes aegypti mosquito, the transmitters of dengue fever, elicited high susceptibility to the ethanolic extract of the seeds with the LC 50 of 224.27 ppm [ 127 ]. A. muricata seeds showed more than five times synergistic larvicidal activity when combined with Piper nigrum fruit ethanolic extracts ( A. muricata 90:10 P. nigrum ) [ 128 ]. The fractionation analysis of the extract showed that n -hexane is the most active fraction with an LC 50 of 73.77 ppm.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Therefore, our results are consistent with other reports in the literature (LEATEMIA; LLANOS;ARANGO;GIRALDO, 2008;GRZYBOWSKI et al, 2013; (COLOM et al, 2008) and insecticidal and anti-feeding activities for Spodoptera frugiperda (J.E. Smith, 1797) larvae .…”
Section: Fungicidal and Antiaflatoxigenic Activity Of The Most Promissupporting
confidence: 93%
“…The study showed that different mechanisms of the two constituents explained the observed synergism and lead to a simple and efficient phytolarvacidal formulation against Aedes aegypti mosquito. [80] Antimicrobial constituents of the essential oil obtained from fresh leaves of Zanthoxylum alatum were analyzed by TLC-direct bioautography and isolated by PLC. For assaying antifungal activity, silica gel 60 F 254 plates developed in hexane-ethyl acetate (9:1) were used for separation, and inoculum spray solution was prepared for test fungi (Alternaria alternata) with liquid potato dextrose.…”
Section: Tlc-msmentioning
confidence: 99%